New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean - Blake, James A. (Zootaxa, 2021)
Six species of Caulleriella (Cirratulidae), four new to science, are reported from continental shelf and slope depths of the western North Atlantic. The majority of new material was collected as part of deep-water reconnaissance and monitoring surveys along the U.S. Atlantic coast from New England to the Carolinas that were intended to understand the potential impacts of oil and gas exploration in poorly known offshore environments. Additional materials from shallow water and shelf habitats off New England and New York as part of other projects are also included. New species include: Caulleriella filiformia n. sp., C. nobska n. sp., C. pintada n. sp., and C. rodmani n. sp. In addition, new records and comments are provided for C. venefica Doner & Blake, 2016 a widespread shelf species and C. sp., a potential new species represented by a few specimens from rocky nearshore New England habitats. The latter may be related to the enigmatic C. fragilis (Leidy, 1855). A review of known deep-water species of Caulleriella is provided.